Media Pembelajaran “Si Sidol” untuk Meningkatkan Keterampilan Membaca dan Menulis Aksara Jawa Kelas VIIA di SMP Negeri 4 Wates - Setyawati, Bethy Mahara (Jurnal Didaktika Pendidikan Dasar, 2019)
The objective of this research is to improve the activeness and success in learning to read and write Javanese letters in class VII SMP Negeri 4 Wates. This research is action research. The research is done in two cycles with the stages: planning, action, observation, and reflection. The subject of the research is class VIIA students of SMP Negeri 4 Wates, 32 students. The data collection technique uses observation, daily notes, and reading and writing Javanese letters skill test. The research instruments are observation sheets, daily notes, and the assessment of reading and writing Javanese letters skill. The data analysis for the learning process uses descriptive qualitative analysis, while the learning success is analyzed with descriptive-quantitative analysis. The result of the research shows that the learning media Si Didol can improve the activeness reading and writing Javanese letters skill of class VIIA  students in SMP Negeri 4 Wates. The result of the observation and field notes show that there is an improvement in students learning activeness. The result of the reading and writing Javanese letters skill assessment also shows improvement, 81% in cycle 1 becomes 94% in cycle 2.